2007
DOI: 10.1016/j.jneuroim.2007.03.022
|View full text |Cite
|
Sign up to set email alerts
|

ICOS gene haplotypes correlate with IL10 secretion and multiple sclerosis evolution

Abstract: Human ICOS is a T cell costimulatory molecule supporting IL10 secretion. A pilot study investigating variations of the ICOS gene 3'UTR detected 8 polymorphisms forming three haplotypes (A, B, C). Haplotype-A and -C displayed the highest difference. Activated T cells from healthy AA homozygotes expressed significantly less ICOS and secreted more IL10 than AC heterozygotes, whereas AB heterozygotes displayed intermediate levels. Analysis of 441 multiple sclerosis patients and 793 controls showed that frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Our study found linkage disequilibria between the polymorphisms ICOSc.602A>C, ICOSc.1624C>T, and ICOSc.2373G>C similar to those described by the Italian group [19] We cannot yet provide an explanation for this finding. As a matter of fact, the AA genotype of the ICOS gene is supposed to impair the expression of ICOS molecule [19] and thus impair the T cell-mediated response and T-cell dependent maturation of B-cells.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Our study found linkage disequilibria between the polymorphisms ICOSc.602A>C, ICOSc.1624C>T, and ICOSc.2373G>C similar to those described by the Italian group [19] We cannot yet provide an explanation for this finding. As a matter of fact, the AA genotype of the ICOS gene is supposed to impair the expression of ICOS molecule [19] and thus impair the T cell-mediated response and T-cell dependent maturation of B-cells.…”
Section: Discussionsupporting
confidence: 50%
“…In the present study, we extended our investigation to subsequent ICOS gene polymorphisms which were recently described as functional ones [17,19] and were shown to be associated with susceptibility to multiple sclerosis [19] and outcome after renal [18] or hematopoietic stem cell transplantation [29], but not to melanoma [30]. [19], the frequency of the AA genotype was significantly lower in MS patients with relapsing-remitting disease than in controls, and those patients had a lower relapse rate and MS severity score.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations